Writing strategies for the common core integrating reading comprehension into the writing process, grades 3-5 - Wolfe, Hillary (North Mankato, MN Maupin House Publishing, Inc, 2016)
Elementary-school students need to learn to write explanatory/informational, argument, and narrative text types and respond to literature, both for standardized tests and, more importantly, real-world writing. With a balanced literacy approach, Wolfe provides core instruction, teaching strategies, and mini-lessons on these text types, each of which can be delivered across content areas or as a complete unit of
English Language
a gift from book africa
1 2 13 15
Keywords: Common Core State Standards (Education); English language -- Composition and exercises -- Study and teaching (Elementary) -- United States; Language arts (Elementary) -- Standards -- United States